A new species of Dalbergia (Fabaceae: Dalbergieae) from Tamil Nadu, India - Soosairaj, S.; Raja, P.; Britto, S. John; Balaguru, B. (Phytotaxa, 2018)
Dalbergia matthewii S. Soosairaj, P. Raja & S. John Britto, a new species from the Western Ghats in South India, is described and illustrated. The species is a liana from the fringes of Southern Montane Wet Temperate Forests. The new species is distinguished from the closely similar species D. gardneriana and D. congesta by its more numerous leaflets (13), larger petiolule (2–4 mm), greenish-yellow flowers, obovate vexillum, strigose hairs along the margin of the ovary and pod that is reticulate throughout. In order to aid in the identification of this new species a key to the scandent species of Dalbergia in India is provided.